Pharmacodynamic equivalence study of two preparations of eye drops containing dorzolamide and timolol in healthy volunteers - Gatchev, Emil; Petrov, Andrey; Kolev, Emil; Hristova, Russka; Demircheva, Irena; Koytchev, Rossen; Richter, Wolfram; Tegel, Friedrich; Thyroff-Friesinger, Ursula (Arzneimittelforschung, 2011)
The aim of the present study was to assess the pharmacodynamic equivalence (lowering of intraocular pressure) of two preparations of eye drops containing 20 mg dorzolamide (CAS 120279-96-1) and 5 mg timolol (CAS 26839-75-8).The study was conducted as a monocentric, observer-blinded, randomized, single-dose, two-period crossover study in 38 healthy volunteers. Each volunteer received on day 1 in each period in a random way a single dose of 1 drop of the test or the reference formulation in the conjunctival sac of the right eye separated by a wash-out period of 7 days. Measurement of intraocular pressure (IOP) of the right eye (by a blinded observer) was performed on day 1 of each study period pre-dose and 2 h post dosing by means of Goldmann applanation tonometry. In order to investigate the pharmacodynamic equivalence of both products, the two-sided 95% confidence interval was calculated for the difference of the primary target parameter (absolute decrease in IOP 2 h post dose), by means of a parametric (ANOVA) statistical method.The results of the statistical evaluation of the primary target parameter “absolute decrease in IOP 2 h post dose” demonstrated a decrease in the IOP of 4.72 mmHg for the eye treated with the test formulation (dorzolamide 20 mg/ml + timolol 5 mg/ml eye drops) and 4.61 mmHg for the eye treated with the reference formulation. The mean difference was 0.11 mmHg. The 95% confidence interval was between −0.33 and 0.55 mmHg and thus entirely within the pre-defined equivalence range (± 1.5 mmHg). The results of the statistical evaluation of the secondary target parameter relative (as% of baseline) decrease in IOP 2 h post dose demonstrated essentially similar effectiveness in lowering the IOP by 27.63% (test formulation) and 27.12% (reference formulation), respectively. Both drug products were well tolerated.Both formulations showed comparable results obtained at a time probably equal to the maximum effect concerning the primary target parameter lowering of IOP 2 h post dose. The safety profile of both preparations showed no difference.
Keywords: Crossover study design; Dorzolamide + timolol; Eye drops; Healthy volunteers; Pharmacodynamic equivalence